Inception Report: Feed the Future for Climate-Smart Cocoa Program - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Cocoa is an important agricultural commodity for rural communities and for the private sector. Cocoa also is a unique crop facing a complex set of challenges, both today and in future. Currently, West Africa accounts for over 70% of global cocoa output involving an estimated two million households, most of them smallholders with three hectares or less. Central America’s cocoa sector is significantly smaller, but production has been increasing rapidly. This region is of growing interest to the private sector, particularly small and medium enterprises. Both regions are facing the global challenge of climate change. Scientific modelling suggests that different cocoa cropping areas may need to change crops and cropping strategies, or adapt management practices, in order to maintain cocoa supply and viable livelihoods. This report therefore examines and the critical concept ofclimate-smart agriculture (CSA), in the case of cocoa. The cocoa industry is most familiar with one key pillar of CSA — sustainably increasing agricultural productivity and smallholders’ incomes. This commitment is driven by their business model and by concerns about economic and social sustainability. Climate change adaptation and mitigation are new on the radar and some new exciting initiatives exist. As climate change alters the core characteristics of agricultural landscapes, it threatens the viability of cocoa production, impacting ‘people, planet and profit’, thereby directly treathening all core cocoa sector interests. Significant opportunities exist to leverage and optimize industry engagement and investments in cocoa sustainability, with a view to adapt, mitigate and build resilience to climate change. Some of these opportunities are more clearly defined than others, which underlines the need for continued joint learning. The Feed the Future Partnership for Climate Smart Cocoa (CSC) Program, supported by USAID and World Cocoa Foundation (WCF) member companies, provides us with the opportunity to work with industry, growers’ organizations, development agencies and national governments, in order to develop strategies for greater cocoa industry engagement in CSA. The CSC Program also aims to identify, tests and bring to scale innovations that enable farm households and the industry to adapt to pressures from climate change without putting forests at risk. This inception report is an attempt to build a common understanding and open up a discussion on key themes in CSA in the cocoa sector so that the stakeholders of the CSC Program can jointly develop sector-wide strategies to test and scale CSA among smallholders in cocoa-producing landscapes of the target countries. The report is a living document and builds on data, information and analysis carried out by WCF and its knowledge partners. We actively invite readers to provide us with their comments, and further contributions to the ongoing discussion.